Disabling amnestic syndrome following stereotactic laser ablation of a hypothalamic hamartoma in a patient with a prior temporal lobectomy☆ - Zubkov, Sarah (Elsevier, 2015)
A 19-year-old man with cortical dysplasia and intractable focal seizures underwent a right temporal lobectomy. A hypothalamic hamartoma was subsequently recognized, and he then underwent MRI-guided stereotactic laser ablation. Unfortunately, he sustained damage to the bilateral medial mammillary bodies and suffered significant memory loss. We review laser ablation therapy for hypothalamic hamartomas and the anatomy of the memory network. We postulate that his persistent memory disorder resulted from a combination of the right temporal lobectomy and injury to the bilateral medial mammillary bodies.